1985
DOI: 10.1002/jcp.1041250304
|View full text |Cite
|
Sign up to set email alerts
|

A stochastic model for mast cell proliferation in culture

Abstract: A birth-death model was developed for the proliferation of mast cells. According to the model, each secondary mast cell colony starts with one proliferative cell. At each generation each cell chooses among three possibilities: 1) division into two proliferative cells; 2) division into two non-proliferative cells; or 3) disappearance. At each step, a non-proliferative cell either does nothing or disappears. A computer simulation of this model could be fitted reasonably well to our data for the size distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 12 publications
1
16
0
Order By: Relevance
“…Analysis of the size of secondary mast cell colonies and computer simulation of a modification of the birth and death model of Till et al (14) also suggested that mast cell proliferation in culture is a stochastic process (29). Ibgether these data are consistent with the notion that both differentiation and proliferation of hemopoietic progenitors are separate stochastic processes.…”
Section: Differentiation Of Stem Cellssupporting
confidence: 55%
“…Analysis of the size of secondary mast cell colonies and computer simulation of a modification of the birth and death model of Till et al (14) also suggested that mast cell proliferation in culture is a stochastic process (29). Ibgether these data are consistent with the notion that both differentiation and proliferation of hemopoietic progenitors are separate stochastic processes.…”
Section: Differentiation Of Stem Cellssupporting
confidence: 55%
“…A simulation model was developed by Rittgen (1983). The stochastic model of mast cell proliferation developed by Pharr et al (1985) assumed a two-type Galton-Watson process including proliferative and nonproliferative cells. Each proliferative cell gives rise to either two proliferative progeny, or two nonproliferative progeny, or it may die.…”
Section: Hemopoiesis and Clonal Cell Populationsmentioning
confidence: 99%
“…[12][13][14] It has been previously suggested that cell lifecycle events may be referred to as stochastic events in theoretical modeling. 5,7,16,17,[23][24][25][26][27]29,32,33 For example, Pharr et al developed a stochastic model for mast cell proliferation in a culture. 23 Vogel et al similarly referred to stem cell development as stochastic events.…”
Section: Introductionmentioning
confidence: 98%
“…5,7,16,17,[23][24][25][26][27]29,32,33 For example, Pharr et al developed a stochastic model for mast cell proliferation in a culture. 23 Vogel et al similarly referred to stem cell development as stochastic events. 32 Gusella referred to the commitment to erythroid differentiation as a stochastic event as well.…”
Section: Introductionmentioning
confidence: 98%